In Auditory Absentia: Music(ology), Modern Art, and Aesthetic Experience - Caddy, Davinia (Intersections, 2020)
Inspired by recent interdisciplinary studies of music and the visual arts, this article is broadly based on the permeable boundaries between the two that are characteristic at the fin de siècle. I concentrate on scenes of music-making depicted on two painted canvases : Pierre Puvis de Chavannes’s Le Chant du berger (1891) and Henri Matisse’s La Musique (1910). The principal aim is to suggest how these illustrations of music and musical performance, as well as critical responses to them, resonate with perspectives from some of the most prominent aesthetic and intellectual concerns of the day. An additional aim is to extend our understanding of live musical engagement, considering what it might mean to obstruct empathetic identification, deny the sensuous properties of sound, and negate aesthetic experience.